Bis(6-methoxy-2-{[tris(hydroxymethyl)methyl-κO]iminomethyl}phenolato-κ(2) N,O (1))nickel(II) dihydrate - Zhou, Tian (International Union of Crystallography, 2009)
In the title compound, [Ni(C(12)H(16)NO(5))(2)]·2H(2)O, the Ni(II) atom is coordinated by four O atoms and two N atoms from the two 6-methoxy-2-{[tris(hydroxymethyl)methyl]iminomethyl}phenolate ligands in a distorted octahedral coordination geometry. O—H⋯O hydrogen bonds link the complexes and uncoordinated water molecules into two-dimensional networks parallel to (001).